Konsep Pemikiran Ekonomi Al-Ghazali: Relevansinya Dengan Perekonomian Di Era Modernisasi - Anggryani, Lisa; Buhari, Ulfah Luthfiyah; Husain, Hukmiah; Kamiruddin, Kamiruddin (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2024)
This research aims to determine and analyze the concept of al-Gazali's economic thought and its relevance to the economy in the current era of modernization. The analytical method used is library research, which involves collecting data from various sources of information, such as previous scientific journals, books, and websites that discuss and present information regarding the concept of economic thought, according to Al-Ghazali. The results of this research show that in the context of modernization, al-Ghazali's principles extend to financial planning, a moderate lifestyle, voluntary trade, and market evolution. Additionally, his teachings influenced the development of the global halal industry, emphasizing the importance of halal production in accordance with Islamic principles. Al-Ghazali's views on the evolution of money and the role of the state in protecting basic needs remain relevant, encouraging countries like Indonesia to adapt and implement practices such as zakat and waqf for the welfare of society, despite facing challenges of aligning financial structures with Islamic principles.